Hubungan Keterlibatan Orang Tua dan Motivasi Membaca dengan Pemahaman Bacaan pada Anak Usia Pembaca Awal - Fadiya Dina Hanifa; Ratna Prayudipta Azarine (Journal on Education, 2023)
Literacy skills are important to develop especially in early reading age children. Based on a literature review, it is known that there is a relationship between parental involvement and reading motivation on reading comprehension in early reading children. The research was conducted on students and guardian parents of class II SDI Raudlatul Jannah with an age range of 7-8 years. Subjects from the target population of this study were determined based on purposive sampling technique. Based on the research results, the relationship between parental involvement and motivation to read with reading comprehension is not significant. The research results may be influenced by the learning methods in schools and the number of research samples.